HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA DI SMA MUHAMMADIYAH 02 MEDAN DENGAN KEJADIAN AKNE VULGARIS - ARDA TILLA; HERVINA .; DIAN ERISYAWANTY; RINNA AZRIDA (JURNAL ILMIAH SIMANTEK, 2020)
Akne vulgaris is a skin disease caused by inflammation of the pilosebaseus follicles and is the most common disease inadolescents aged 15-18 years. Akne vulgaris sufferers generally complain of aesthetic complaints. The lack of knowledgeand attitude of adolescents towards akne vulgaris can lead to the number of adolescents suffering from akne vulgaris. Thepurpose of this research is to find out the relationship of the level of knowledge and attitude of teenagers at SmaMuhammadiyah 02 Medan with the incident akne vulgaris. This research is descriptive of analytics with cross-sectionaldesign. The subjects in this study are students of Muhammadiyah High School 02 Medan. The technique in this study is touse simple random sampling and data analysis using chi square test. Data retrieval through questionnaire filling. Theknowledge level test of Muhammadiyah High School students 02 Medan about akne vulgaris is majority categorized enough(48.4%) and attitude test results against akne vulgaris the majority are well categorized (66.7%). Chi-Square statistical testresults, the relationship between knowledge level and attitude with akne vulgaris event was obtained a value of p = 0.877(p>0.05) and p = 0.000 (p<0.05). There is no relationship between the level of knowledge and the occurrence of aknevulgaris, and there is a relationship between attitude and the occurrence of akne vulgaris.